Aerobic Granulation in a Sequencing Batch Reactor for the Treatment of Piggery Wastewater. (1st March 2013) - Zhang, Dalei; Wang, Yanan; Li, Hongwei; Wang, Shaoran; Jing, Yumei
Abstract : This study investigated the formation of aerobic granules fed with digested piggery wastewater. After 42 days of cultivation, small yellow granules with mean diameter of 0.4 mm were first observed in the reactor. Scanning electron microscope pictures showed the granules were compact, round structures with clear outer shapes and mainly composed of filamentous bacteria. Maximum chemical oxygen demand and ammonia removal ratios were 90.1 and 91.7%, respectively. The Monod equation, which was used to describe ammonium utilization, yielded a maximum rate of 6.25 mg (g volatile suspended solids) −1 h −1 . The measurement of extracellular polymeric substances (EPS) content and three‐dimensional excitation and emission matrix results showed that the EPS concentration increased during the granulation process. Fluorescence in situ hybridization analysis showed significant amounts of nitrifying bacteria in the aerobic granules. Results in this study provide insights to the treatment of piggery wastewater using aerobic granular sludge.